RELATIONSHIP BETWEEN NUTRITIONAL STATUS WITH GROWTH AND DEVELOPMENT AT 0-12 MONTHS OF INFANT AGE AT POSYANDU MLINJO VILLAGE SUMBERKEPUH DISTRICTS TANJUNG ANOM NGANJUK - Sutik; Indah Maulida; Anik Nuridayanti (Indonesian Health Literacy Journal, 2024)
Growth and development of the brain at an early age will improve skills so that baby can remember things and be able to analyze a problem. Nutritional status with growth and development has the ability in infants aged 0 to 12 months, where at that age baby begin to remember and analyze several things such as names, faces, terms, light, and color. The research objective was to determine the relationship between nutritional status and infant development and growth. The research design is non-experimental observation with a correlational design or analytical survey with the results of the spearman rank statistical test using bivariate. The population of all babies aged 0-12 months at the Posyandu Mlinjo were 20 respondents with a total sampling technique of 20 respondents. The independent variable is nutritional status, and the independent variable is growth and development. The instrument used was observation and sheets to KMS and sheets etc. The sample of this study were all baby aged 0-12 months, as many as 20 baby. The results showed that almost all of them had good nutritional status as many as 16 respondents (80%), for all normal growth rates as many 17 respondents (85%), and almost all the 20 respondents the normal development level was 17 respondents (85%). Shows that there is a relationship between nutritional status and growth and development at infant age based on the results of the Spearman rank statistical test obtained p value = 0,000 ≤ α = 0,05 dan r = 0,840 so that Ha accepted and Ho rejected. The conclusion of this study is that there is a relationship between nutritional status and infant growth and development at 0-12 months of age at Posyandu Mlinjo village Sumberkepuh, district Tanjunganom with a very strong correlation. For that, it is expected to maintain or continue to improve good nutritional status and normal developmental growth.